PENGARUH PANDEMI COVID-19 TERHADAP HASIL PENDAPATAN MASYARAKAT NELAYAN DI DESA PERCUT DUSUN XVI - Friska Putri Aryanti; Lailan Safitri Barus; Mia Audina; Muhammad Irwan Padli Nasution (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
Covid-19 is a disease outbreak that affects all components of human life. The implementation of social/physical distancing, PSBB, lockdown in breaking the chain of the spread of Covid-19 affects the movement of people and goods, especially parts of the marketing sector such as fisheries. This impact certainly has a major impact on fisheries actors such as fishermen. This study aims to determine the impact of the Covid-19 outbreak on the income results of fishermen in Desa Percut. The method used in this research is a case study of fishermen who had an impact on the Covid-19 outbreak in Percut Village. Data obtained from interviews and direct observation by purposive sampling. The impactf the COVID -19 outbreak on fishermen in the lack of publick interest, in buying fish, low selling prices of fish, reduced distributors, reduced number of crew members and decreased salaries of crew members.